IMPLEMENTATION OF HUMAN RESOURCE STRATEGIES IN COFFEE SHOPS BACKPAGE: IMPLEMENTATION OF HUMAN RESOURCE STRATEGIES IN COFFEE SHOPS HALAMAN BELAKANG - Salsabila, Frsylia (UPMI Proceeding Series, 2023)
Researchers in conducting research want to know the implementation of the Halaman Belakang Coffee Shop strategy. The research was conducted at the Halaman Belakang Coffee Shop which is engaged in food and baverage or culinary. The purpose of the strategy that Coffee Shop Halaman Belakang has in managing human resources so that the activities carried out run effectively and efficiently. The strategy applied by this Coffee Shop in managing human resources by implementing a semi-formal system, namely by creating a family atmosphere which aims to provide a sense of comfort for employees in carrying out their work. The performance appraisal carried out by the Halaman Belakang Coffee Shop uses descriptive data analysis methods of data from interviews, surveys, observations and notes in the field collected through a list of questions that have been prepared with a case study approach. Based on the research results, it can be concluded that Coffee Shop has implemented strategies such as: structure and division of tasks, selection process and employee criteria, training and coaching, Reward System, and Rotation or transfer of employee positions which aims to maximize employee performance and create job satisfaction felt by employees while carrying out their work.